Impact of Mudharabah and Murabahah Financing on Profitability of Islamic Banks in Indonesia and Malaysia - Yuliana Mayu Nur Safitri; Rofiul Wahyudi; Nani Hanifah (Green Economics Review, 2024)
In countries with a majority Muslim population, Islamic banks have the ability to easily develop rapidly, including Indonesia and Malaysia. Therefore, it cannot be denied that Indonesia and Malaysia are countries that are highly focused on the development of Islamic banking. It can be seen in terms of asset growth which is increasing every year, which is proof that Islamic banks in Malaysia and Indonesia have succeeded in achieving positive performance which affects the bank's profitability. This research aims to analyze the influence of mudharabah and murabahah financing on the profitability of Indonesian and Malaysian sharia banks partially or simultaneously. The data analysis technique used is descriptive. The type of data obtained from this research is secondary data based on the annual reports of Indonesian and Malaysian Sharia Banks for the period 2016 to 2020. By using a purposive sampling technique, 17 Islamic banks were sampled. This research uses data analysis tests of classical assumptions and hypotheses. The research results show that partial mudharabah financing has no effect on the profitability of Indonesian and Malaysian sharia banks. Murabahah financing partially influences the profitability of Indonesian and Malaysian sharia banks. Meanwhile, mudharabah and murabahah financing simultaneously influence the profitability of Indonesian and Malaysian sharia banks.